On the Administrative Law Protection of Personal Information in the Era of Big Data - Zhang, Siyu (Journal of Artificial Intelligence and Information, 2025)
In the era of big data, the security and privacy of personal information face new challenges, and the diversity of data sources and large-scale collection methods increase the risk of information leakage. Administrative law demonstrates higher efficiency and flexibility in protecting personal information compared to civil law and criminal law. By regulating the information processing procedures of administrative agencies, strengthening regulatory systems, and improving relief mechanisms, it helps to more effectively protect personal information. At the same time, the transformation of government information disclosure and data sharing has prompted administrative law to play an important role in balancing personal privacy and public interest. This article explores the necessity, current issues, and optimization paths of personal information protection in the era of big data from the perspective of administrative law.